Zeolite Y: Synthesis, Modification, and Properties—A Case Revisited - Wolfgang Lutz (Advances in Materials Science and Engineering)
Y zeolites dealuminated by steaming were introduced as fluid-cracking catalysts in the year 1970. Extensive research has been done to develop suitable dealumination techniques, to investigate crystal structure, and to characterize catalytic behaviour. However, the origin of the secondary pore system formed in the zeolite structure during dealumination process remained completely obscure over a period of four decades. Open questions concerned also the existence of extraframework siliceous admixture in addition to extraframework aluminium species which can dramatically change the catalytic properties of these zeolites. This paper gives a review on the synthesis of DAY materials and provides some answers to several open questions.